Study on Survey and Reclamation of Ravines in India - Planning Commission (Planning Commission, 1965)
The total extent of ravine lands in India is about 3 million hectares. The problem of such lands is acute in the States of Madhya Pradesh, Uttar Pradesh, Rajasthan and Gujarat. In addition considerable area known as marginal lands is in a state of acute erosion which requires immediate attention, if it is to be prevented from coming under ravines. The magnitude of the problem can be gauged when one knows that the rate of ravine formation is of the order of 3,000 acres per year in Madhya Pradesh alone. These critical areas need immediate handling not only for preventing further formation of ravines but also for the reclamation of existing ravines for useful production. The land reclaimed from the ravines should be put to the use depending upon its use capability. It has been stressed in the study that deep ravines should be put under forest. I do hope that the recommendations made in the study will be found useful by the State Governments concerned and will receive immediate attention.
Committee on Natural Resources Planning Commission New Delhi